CLINICAL CHARACTERISTICS AND SURGICAL OUTCOMES OF MANDIBULAR THIRD MOLAR EXTRACTION IN CADETS AT THE VIETNAM MILITARY MEDICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical characteristics, radiographic features, and surgical outcomes of mandibular third molar extraction in cadets at the Vietnam Military Medical University.Methods: A cross-sectional descriptive study with analytical components, combined with a prospective approach, was conducted on 90 patients undergoing surgery at Military Hospital 103. Clinical, radiographic, and postoperative outcome data were collected and analyzed using Stata 15.0 software.Results: Common symptoms included pain (45.6%), food impaction (30%), and occlusal discrepancy (53.3%), with a high prevalence of gingivitis (90.6%). Radiographically, most third molars were mesioangularly impacted (78.9%), classified as depth A (76.7%), with bifurcated roots (73.3%), and predominantly located away from the inferior alveolar canal (93.4%). The mean surgical difficulty score was 7.0 ± 0.8. Intraoperative complications included root fracture (7.8%) and flap tearing (24.4%), with no severe complications observed. Postoperative outcomes showed marked improvement: 91.1% of cases were rated as good at day 7, and 100% at day 30. Mouth opening progressively increased, and pain scores significantly decreased over time.Conclusions: In young adults, mandibular third molars are predominantly mesioangularly impacted, presenting relatively high surgical difficulty; however, treatment outcomes are favorable with a low complication rate. Comprehensive preoperative assessment and appropriate surgical techniques are essential for optimizing clinical outcomes
Keywords: Mandibular third molar, wisdom tooth extraction, surgical